Rejestry nieruchomości w dawnej Polsce - Dariusz Felcenloben (Czasopismo Prawno-Historyczne)
The paper outlines the history of land cadastres and land and mortgage registers in Poland from the earliest times until the fi rst Partition. Against the background of the changing principles of establishing ownership, transferring or encumbering it with rights in rem or creating obligations over it, the paper describes how land and mortgage registers developed. They were modern public registers, which introduced the Polish mortgage into the legal system. Its design was far ahead of the legislation of most European countries at that time. The novelties included the principles of free access to, and reliability of, a mortgage, its legality, freedom of encumbrance, detailed character, priority of entry and, fi nally, the principle of good faith of registers.